Buriti pie (Mauritia flexuosa) as an alternative ingredient in rations for juveniles of Tambaqui (Colossoma macropomum) (Research, Society and Development, 2021)
In this work, the effect of including increasing levels of buriti pie (Mauritia flexuosa) on production parameters and economic viability was studied. In this experiment 360 fish with an initial average weight of 7.7 ± 2.8 g were distributed in nine water tanks with a capacity of 360 liters each, in a completely randomized experimental design, with three inclusion treatments of buriti pie flour (0; 15; 30%) and three repetitions. Over a period of 60 days, the physical and chemical parameters of the water were measured: temperature, dissolved oxygen, pH, total ammonia, hardness and nitrite. And the zootechnical performance of the juveniles was measured through the apparent feed conversion indices, final weight, specific growth rate, daily weight gain and survival. Economic viability was determined by analyzing the average cost of food per kilogram of live weight gained. The results were submitted to analysis of variance (One way ANOVA) and the means of each treatment compared by Tukey test, at the level of 5% probability. The values for the studied variables did not show significant difference between the treatments, but there is a trend of worsening in feed conversion with the increase in the inclusion of buriti pie. It was concluded that the inclusion of the pie in the diet did not reduce the production costs and that the inclusion of buriti pie in the diet of Tambaqui juveniles is unfeasible.